A STUDY ON TEACHER’S COMMUNICATION STRATEGIES IN TEACHING AND LEARNING PROCESS - Alvienna Sifa Maulida Nasution; Atonso Hasibuan; Sri Henni Br Saragih; Sondang Manik; Lastri Wahyuni Manurung (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Communication is important for people around the world. Without communication, people will not be able to communicate each other. In understanding some different languages, people need to learn the target language to communicate with, for instance Indonesian people learn to acquire English. In the context that English in Indonesia is considered as foreign language, it causes the learners understand not only the language but also the culture. In order to convey their messages and remain in a conversation until their communication goal is achieved, ESL (English as a Second Language) learners need to employ communication strategies, which have been defined generally as devices used by second language by second language learners to achieved specific communication goals. This study was aimed to find teacher communication strategies during classroom interaction. The use of those communication strategies is underlying two main reason which are solving the speaking problems and making interactive speaking and learning situation. Teachers used various communication strategies to stimulate learners to be more active during the teaching and learning process.